Pengaruh Tingkat Literasi Keuangan Syariah terhadap Keputusan Menggunakan Lembaga Keuangan Syariah (Studi pada Dosen UIN Ar-Raniry) - Dahlia, Muna; Ibrahim, Azharsyah; Riza, Akmal (Share: Jurnal Ekonomi dan Keuangan Islam, 2020)
The Impact of Islamic Financial Literacy on Lecturers’ Decision-Making in Utilizing Islamic Financial Institutions: Evidence from UIN Ar-Raniry - Islamic financial literacy is an extension of financial literacy, encompassing individuals' knowledge and understanding of financial concepts in accordance with Sharia principles. Low levels of Islamic financial literacy can affect the quality of financial decision-making, including decisions to use Islamic financial institutions. This study aims to analyze the influence of Islamic financial literacy on decisions to use Islamic financial institutions among lecturers at Universitas Islam Negeri (UIN) Ar-Raniry. The research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to 86 lecturers, selected via accidental sampling from the total population of lecturers at UIN Ar-Raniry. Data analysis was conducted using simple linear regression with the assistance of SPSS software. The results show that Islamic financial literacy has a positive and significant effect on decisions to use Islamic financial institutions. This is evidenced by a regression coefficient of 0.171 and a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.284 indicates that Islamic financial literacy accounts for 28.4% of the variance in decisions to use Islamic financial institutions, while the remaining 71.6% is influenced by other factors not covered in this study. The study concludes that the higher the level of Islamic financial literacy among lecturers, the better their decisions regarding the use of Islamic financial institutions. The implications of this study highlight the importance of improving Islamic financial literacy among lecturers to encourage the use and development of Islamic financial institutions.